Zagadnienie imienia w opowiadaniu Antona Czechowa „Czarny mnich” - Shubin, Roman (Studia Rossica Posnaniensia, 2012)
The anthroponyms of two heroes, Kovrin and Pesotsky, are analyzed in Anton Chekhov’s The Black Monk. Despite the conditional landscape and philosophical discourse of the story it is possible to analyze these names from linguistic, intertextual and art-interpretative positions. Also, the precedential names enrich this research.